Interface Modification Uncovers the Potential Application of SnO2/TiO2 Double Electron Transport Layer in Efficient Cadmium‐Free Sb2Se3 Devices. Issue 13 (18th March 2022) - Wang, Weihuang; Yao, Liquan; Dong, Jiabin; Wu, Li; Cao, Zixiu; Hui, Li; Chen, Guilin; Luo, Jingshan; Zhang, Yi
Abstract: An undesirable p–n heterojunction interface of Sb2 Se3 absorber with Cd‐free electron transport layer (ETL) is one of the key problems hindering the efficiency improvement of Sb2 Se3 solar cell. Herein, a promising SnO2 /TiO2 ETL coupled with SbCl3 treatment is introduced to improve the performance of Sb2 Se3 solar cell. The mechanism of SbCl3 treatment on the crystal orientation of Sb2 Se3 thin film and the p–n heterojunction interface of Sb2 Se3 solar cell is disclosed combined with different characterization methods. The carrier transport property for Sb2 Se3 thin film is enhanced, and the conduction band offset (CBO) of TiO2 /Sb2 Se3 interface is reduced from 0.57 to 0.20 eV by forming Sb2 O3 interlayer at TiO2 /Sb2 Se3 interface after SbCl3 treatment, by which the interface recombination and the open circuit voltage deficit of the device can be effectively decreased, and the interface bonding at TiO2 /Sb2 Se3 interface can be effectively improved. Ultimately, the Cd‐free Sb2 Se3 solar cell with configuration of ITO/SnO2 /TiO2 /Sb2 Se3 /Au achieves an efficiency of 5.82%, which is the highest efficiency in vapor transport deposition (VTD)‐processed Cd‐free Sb2 Se3 solar cell at present. This work is expected to fill in the blank of VTD‐processed Cd‐free Sb2 Se3 solar cell and offers a valuable reference for future band alignment of Sb2 Se3 solar cell. Abstract : The SnO2 /TiO2 surface is modified with SbCl3 solution, by which Sb2 O3 ‐modified SnO2 /TiO2 composited electron transport layer is formed. The conduction band alignment of Sb2 Se3 solar cell and the perpendicular crystal orientation of Sb2 Se3 thin film is tailored by SbCl3 treatment. Ultimately, Sb2 O3 ‐modified SnO2 /TiO2 ETL leads to VTD‐processed Cd‐free Sb2 Se3 solar cell efficiency of 5.82%.